Iodine status of Eeyou Istchee community members of northern Quebec, Canada, and potential sources. Issue 4 (12th March 2015) - Tam, Benita; Tsuji, Leonard J. S.; Martin, Ian D.; Liberda, Eric N.; Ayotte, Pierre; Coté, Suzanne; Dewailly, Éric; Nieboer, Evert
Abstract : Comparison of urinary iodine concentrations and iodine/creatinine ratios for six Canadian indigenous communities. Abstract : A multi community environment-and-health study among six of the nine communities of Eeyou Istchee in northern Quebec, Canada provided greater insight into iodine intake levels among these Cree First Nation communities. Using data from this large population-based study, descriptive statistics of measured urinary iodine concentrations (UICs) and iodine–creatinine ratios (stratified by age, sex, community of residence, and water consumption) were calculated, and the associations between independent variables and iodine concentration measures were examined through a general linear model. Traditional food consumption contributions were examined through Pearson partial correlation tests and linear regression analyses; and the importance of water sources through ANOVA. Generally speaking, urinary iodine levels of Eeyou Istchee community members were within the adequate range set out by the World Health Organization, though sex and community differences existed. However, men in one community were considered to be at risk of iodine deficiency. Older participants had significantly higher mean iodine–creatinine ratios than younger participants (15–39 years = 90.50 μmol mol −1 ; >39 years = 124.52 μmol mol −1 ), and consumption of beaver ( Castor canadensis ) meat, melted snow and ice, and bottled water were predictive of higher iodine excretion. It is concluded that using both urinary iodine indicators can be helpful in identifying subgroups at greater risk of iodine deficiency.